ADCP Gothenburg 2018 - Arneborg, Lars; Nylund, Amanda; Hassellöv, Ida-Maja; Tengberg, Anders (Chalmers University of Technology, 2021)
Note: This is version two of the data set. In a previous version (https://doi.org/10.5281/zenodo.5066997), the vertical beam velocities were missing.

A bottom mounted mooring with a fixed upward-looking Nortek Signature 500 ADCP was deployed under the ship lane to Gothenburg Harbour at 32 m depth, position (57.61178 N, 11.66102 E) in the period 28 August to 25 September 2018. The ADCP was set up to measure and store single ping, along beam current velocities, using four slanted beams (25° angle) and one vertical beam (ping frequency 1 Hz, vertical cell size 1 m on all beams). The instrument was set up with 38 bins numbered from 1 to 38 with #1 closest to the instrument centered 1 m above the transducers.

The data set contains raw data from the instrument, converted to csv format with the Nortek Deployment software.

Processing: This is raw data, so no processing has been performed.

Notes:

- Beam #2 is not working, so those data do not make sense.

- Data from about 10% of the depth below the surface and above should not be used.

Files:

*#B0_#.csv: Data from the four slanted beams. Each row is one ping. Header in first row.

*#IB0_#.csv: Data from the vertical beam. Each row is one ping. Header in first row.

Parameters:

DateTime: Date and time in format MM/DD/YYYY hh:mm:ss

Ensemble: Ping number

Battery: Battery voltage

Heading: Instrument heading in deg.

Pitch: Instrument pitch in deg.

Roll: Instrument roll in deg.

Pressure: Pressure in dBar

Temperature: Temperature in deg C.

Vel#N: Vertical beam velocity (m/s) for bin N

VelM#N: Beam velocity (m/s) for beam M and bin N

Amp#N: Vetical beam amplitude for bin N

AmpM#N: Beam amplitude for beam M and bin N

CorrM#N: Correlation for beam M and bin N

AltimeterDistanceLE: Distance from transducer to surface (m)
Keywords: ADCP; raw ping data; ship lane; Transport Systems and Logistics; Transportteknik och logistik